Rapid gene expression change in a novel synthesized allopolyploid population of cultivated peanut×Arachis doigoi cross by cDNA-SCoT and HFO-TAG technique - Liang-qiong HE; Rong-hua TANG; Jing JIANG; Fa-qian XIONG; Zhi-peng HUANG; Hai-ning WU; Zhong-kui GAO; Rui-chun ZHONG; Xin-hua HE; Zhu-qiang HAN (Journal of Integrative Agriculture, 2017)
Allopolyploidy has played an important role in plant evolution and heterosis. Recent studies indicate that the process of wide hybridization and (or) polyploidization may induce rapid and extensive genetic and epigenetic changes in some plant species. To better understand the allopolyploidy evolutionism and the genetic mechanism of Arachis interspecific hybridization, this study was conducted to monitor the gene expression variation by cDNA start codon targeted polymorphism (cDNA-SCoT) and cDNA high-frequency oligonucleotide-targeting active gene (cDNA-HFO-TAG) techniques, from the hybrids (F1) and newly synthesized allopolyploid generations (S0–S3) between tetraploid cultivated peanut Zhongkaihua 4 with diploid wild one Arachis doigoi. Rapid and considerable gene expression variations began as early as in the F1 hybrid or immediately after chromosome doubling. Three types of gene expression changes were observed, including complete silence (gene from progenitors was not expressed in all progenies), incomplete silence (gene expressed only in some progenies) and new genes activation. Those silent genes mainly involved in RNA transcription, metabolism, disease resistance, signal transduction and unknown functions. The activated genes with known function were almost retroelements by cDNA-SCoT technique and all metabolisms by cDNA-HFO-TAG. These findings indicated that interspecific hybridization and ploidy change affected gene expression via genetic and epigenetic alterations immediately upon allopolyploid formation, and some obtained transcripts derived fragments (TDFs) probably could be used in the research of molecular mechanism of Arachis allopolyploidization which contribute to thwe genetic diploidization of newly formed allopolyploids. Our research is valuable for understanding of peanut evolution and improving the utilization of putative and beneficial genes from the wild peanut.